Trends Of Sitting Volleyball Players Towards The Incentive System And Its Relationship To Players’ Performance - A Field Study Of The Teams Of The First National Division In Algeria For The Physically Disabled - Aitmouheb, Amine; Yakhlef, Ahmed (sports creativity, 2025)
This study aims to find out the trends of sitting volleyball players on the incentive system and its relationship to player performance, through various theoretical backgrounds. The study has produced many results, including developing and improving the performance of its players by searching for ways and methods that raise its activities and morale, Making the player raise his level and his performance and to know the trends of players on the incentive system from raising the level of performance using the descriptive approach so that a sample consisting of 45 sitting volleyball players out of 8 teams the study was conducted using of trends towards incentives and the scale of performance and the results were analyzed using spss22 system reaching the result : the existence of relationship between the moral and material incentives and performance of the players .